MiR-654-3p Constrains Proliferation, Invasion, and Migration of Sinonasal Squamous Cell Carcinoma via CREB1/PSEN1 Regulatory Axis - Cui, Xiao; Yang, Ying; Yan, Aihui (Frontiers in Genetics, 2022)
Background: MiR-654-3p can repress malignant progression of cancer cells, whereas no relative reports were about its modulatory mechanism in sinonasal squamous cell carcinoma (SNSCC). This research committed to approaching modulatory effect of miR-654-3p on SNSCC cells. Methods: Bioinformatics methods were utilized for analyzing interaction of miR-654-3p/CREB1/PSEN1. Expression levels of miR-654-3p, CREB1, and PSEN1 mRNA were assessed by qRT-PCR. Western blot was completed for level assessment of CREB1, PSEN1, and epithelial-mesenchymal transition-related proteins. The targeted relationship between miR-654-3p and CREB1, or CREB1 and PSEN1 was authenticated via dual-luciferase assay and ChIP assay. A trail of experiments in vitro was employed for detection of the effects of miR-654-3p/CREB1/PSEN1 axis on malignant progression of SNSCC cells. Results: CREB1 as the downstream target mRNA of miR-654-3p could activate transcription of its downstream target gene PSEN1. Besides, miR-654-3p could target CREB1 to repress PSEN1 expression, thus restraining proliferation, migration, invasion, epithelial-mesenchymal transition, and hastening apoptosis of SNSCC cells. Conclusion: MiR-654-3p as an anti-tumor gene targeted CREB1 to hamper malignant progression of SNSCC through miR-654-3p/CREB1/PSEN1 axis. Keywords: miR-654-3p; CREB1; PSEN1; sinonasal squamous cell carcinoma; malignant progression; Epithelial-mesenchymal transition